Pairing of sexual and asexual generations of Nearctic oak gallwasps, with new synonyms and new species names (Hymenoptera: Cynipidae, Cynipini) - Nicholls, James A.; Melika, George; Digweed, Scott C.; Stone, Graham N. (Zootaxa, 2022)
Most oak gallwasps (Hymenoptera; Cynipidae, Cynipini) have lifecycles involving obligate alternation between a sexual and an asexual generation. Many species are currently known from only one of these generations, with the alternate generation either unknown or separately described with a different name. Here we describe previously unknown generations for 12 Nearctic oak cynipids. We describe the sexual generation for ten species previously known only from an asexual generation: Acraspis quercushirta (Bassett, 1864), Acraspis villosa Gillette, 1888, Amphibolips spinosa Ashmead, 1887, Andricus balanaspis (Weld, 1922), comb. nov., Antron quercusnubila (Bassett, 1881), Bassettia pallida Ashmead, 1896, Neuroterus floccosus (Bassett, 1881), comb. rev., Philonix fulvicollis Fitch, 1859, Phylloteras poculum (Osten Sacken, 1862) and Sphaeroteras carolina (Ashmead, 1887), comb. rev.. We describe the asexual generation of Bassettia flavipes (Gillette, 1889), comb. nov. and Melikaiella tumifica (Osten Sacken, 1865), both previously known only from a sexual generation. Three described taxa (Neuroterus vernus Gillette, 1889, syn. nov., Neuroterus papillosus Beutenmueller, 1910, syn. nov. and Neuroterus perminimus Bassett, 1900, syn. nov.) are all identified as the sexual generation of Neuroterus niger Gillette, 1888. We also comment on the presence of previously unknown non-functional males reared from galls of the asexual generation of Neuroterus niger. We identify two further synonyms: Acraspis macrocarpae Bassett, 1890 is syn. nov. of A. quercushirta (Bassett, 1864), and Bassettia archboldi Melika & Abrahamson, 2007 is syn. nov. of Bassettia pallida Ashmead, 1896. In addition, we formally synonymise multiple varieties described by Kinsey within his Acraspis quercushirta, A. villosa, Antron quercusnubila, Neuroterus niger and Philonix fulvicollis species complexes. We provide descriptions and diagnoses for these taxa, and summarise what is known of their biology, including host associations. All taxa and relationships between alternate generations are supported by morphological and molecular data.